2002
DOI: 10.1159/000064556
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Arachidonate Metabolism in Human Epidermoid Carcinoma A431 Cells Overexpressing Phospholipid Hydroperoxide Glutathione Peroxidase

Abstract: Phospholipid hydroperoxide glutathione peroxidase (PHGPx), a selenium-dependent glutathione peroxidase, can interact with lipophilic substrates, including phospholipid hydroperoxides, fatty acid hydroperoxides and cholesterol hydroperoxides, and can reduce them to hydroxide compounds. It also seems to be a major regulator of lipid oxygenation in human epidermoid carcinoma A431 cells. In order to study the functional role of PHGPx in the regulation of 12-lipoxygenase and cyclooxygenase, cDNA of PHGPx was insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…90,91 Experiments with human epidermoid carcinoma A431 cells that were transfected with the cDNA sequence of cytoplasmic PH-GPx revealed that PH-GPx downregulates the 12-LOX activity. 92 In animals, platelets 12-LOX, 15-LOX and COX-2 are more sensitive to PH-GPx inhibition than do 5-LOX and COX-1, which are more resistant. 93 This inhibition is probably caused by a requirement of fatty acid hydroperoxides for the activation of LOX and COX that are regulated by its own products.…”
Section: Sources Of Free Radicals During Inflammationmentioning
confidence: 99%
“…90,91 Experiments with human epidermoid carcinoma A431 cells that were transfected with the cDNA sequence of cytoplasmic PH-GPx revealed that PH-GPx downregulates the 12-LOX activity. 92 In animals, platelets 12-LOX, 15-LOX and COX-2 are more sensitive to PH-GPx inhibition than do 5-LOX and COX-1, which are more resistant. 93 This inhibition is probably caused by a requirement of fatty acid hydroperoxides for the activation of LOX and COX that are regulated by its own products.…”
Section: Sources Of Free Radicals During Inflammationmentioning
confidence: 99%
“…Using an intact cell assay system, the metabolism of arachidonic acid to PGE 2 catalyzed by cyclooxygenase 1 was significantly decreased in stable transfectants overexpressing PHGPx when compared to that in a vector control cell line [6]. If the intact cell assay is carried out in the presence of 13-HPODE as a stimulator of lipid peroxidation, formation of 12(S)-hydroxyeicosatetraenoic acid [12(S)-HETE] from arachidonic acid is also significantly decreased in stable transfectants of overexpressing PHGPx when compared to that in a vector control cell line, indicating that PHGPx downregulates the 12(S)-lipoxygenase activity in A431 cells [6]. In accordance with our results in the study of 12(S)-lipoxygenase and cyclooxygenase 1, overexpression of PHGPx in RBL-2H3 cells also significantly suppresses the production of 5-lipoxygenase-catalyzed leukotrienes [25] and cyclooxygenase 2-catalyzed PGD 2 [45].…”
Section: Overexpression Of Phgpx Inhibits Arachidonate Oxygenation Inmentioning
confidence: 99%
“…The basal production of PGE 2 by A431 cells is from the metabolism of arachidonic acid by cyclooxygenase 1 since PGE 2 formation is inhibited by the treatment of the cells with indomethacin but not by the specific cyclooxygenase 2 inhibitor NS398 [7]. Using an intact cell assay system, the metabolism of arachidonic acid to PGE 2 catalyzed by cyclooxygenase 1 was significantly decreased in stable transfectants overexpressing PHGPx when compared to that in a vector control cell line [6]. If the intact cell assay is carried out in the presence of 13-HPODE as a stimulator of lipid peroxidation, formation of 12(S)-hydroxyeicosatetraenoic acid [12(S)-HETE] from arachidonic acid is also significantly decreased in stable transfectants of overexpressing PHGPx when compared to that in a vector control cell line, indicating that PHGPx downregulates the 12(S)-lipoxygenase activity in A431 cells [6].…”
Section: Overexpression Of Phgpx Inhibits Arachidonate Oxygenation Inmentioning
confidence: 99%